Crude Protein and Crude of Fiber Benggala [Panicum Maximum] and Elephant [Pennisetum Purpureum] Grasses on Drought Stress Condition - Purbajanti, ED; Anwar, S; Widyati, S; Kusmiyati, F (ANIMAL PRODUCTION, 2009)
Knowledge of crop response to water is essential for  proper irrigation management. Research  was conducted at Forage Crop Laboratory of Animal Nutrition Department, Faculty Of Animal Husbandry, Diponegoro University  during 9 month  trying two type grass that  were benggala ( Panicum maximum) and elephant  ( Pennisetum purpureum) with treatment of the following dry stres : S0 = control, without  stress; S1 =  1 times drought stress,  S2 =  2 times drought stress  , and S3 =  3 times  drought stress by lay out of complete random design( factorial pattern). Parameter perceived were( 1) forage production , (2) dry matter production, (3) percentage of crude protein, and (4) percentage of crude fibre. Data collected to be analysed  by analysis of varians  continued with Duncan multiple range test. Result of research indicate that forage production of  elephant grass  (103,79 g/pot) bigger than  benggala (53,08 g/pot). Dry matter production of elephant grass was   18,77 g/pot  higher than  benggala  grass( 14,54 g/pot).  Drought stres do not affect to forage  production  also  dry matter production : Percentage of crude protein  of  benggala grass (9,10%) higher than elephant grass (7,02%), while percentage crude fibre of benggala grass (35,64%) higher than elephant grass (31,67%). Drought stres do not influence percentage of crude protein  and crude fibre of benggala and elephant grasses. Conclusion from research were (1) elephant grass  have higher forage production  and  dry matter production than benggala grass (2) percentage of crude protein and crude fibre of benggala grass  higher  than elephant grass, (3) drought stres do not  affect to forage production , dry matter production, percentage of crude protein  and crude fibre. (Animal Production 11(2): 109-115 (2009) Key Words : crude protein, fiber, drought stress